Expression of ChAT, Iba-1, and nNOS in the Central Nervous System following Facial Nerve Injury - Jae Min Lee; Myung Chul Yoo; Yong Jun Kim; Sung Soo Kim; Seung Geun Yeo (MDPI AG, 2024)
Facial nerve injury can cause significant functional impairment, impacting both the peripheral and central nervous systems. The present study evaluated changes in facial motor function, numbers of cholinergic neurons and microglia, and nNOS levels in the facial nucleus of the central nervous system (CNS) following peripheral facial nerve injury. Facial nerve function, as determined by eyeblink and whisker-movement reflexes, was evaluated at baseline and 1, 2, 3, 4, 8, and 12 weeks after inducing facial nerve injury through compression or axotomy. The expression of choline acetyltransferase (ChAT), ionized calcium-binding adaptor molecule 1 (Iba-1), and neuronal nitric oxide synthase (nNOS) in the facial nucleus of the CNS was analyzed 2, 4, and 12 weeks after peripheral facial nerve injury. Compression-induced facial nerve injury was found to lead to temporary facial motor impairment, whereas axotomy resulted in persistent impairment. Moreover, both compression and axotomy reduced ChAT expression and increased Iba-1 and nNOS expression in the facial nucleus, indicating upregulation of an inflammatory response and neurodegeneration. These results indicate that, compared with compression-induced injury, axotomy-induced facial nerve injury results in greater facial motor dysfunction and more persistent microglial and nitric oxide activation in the facial nucleus of the CNS.